Penegakan Hukum Pidana dalam Penanganan Tindakan Pidana Pencurian Tabung Gas 3 Kg di Tembilahan Riau - Rafki Wijaya (Universitas Islam Indragiri, 2025)
Theft is a crime that takes someone else's property illegally and without the consent of the owner of the goods. theft cases, theft is an act of stealing carried out by someone by taking an item or something similar belonging to someone else in violation of the law. Testimony is an element in theft cases that have been explained in Article 362 of the Criminal Code. In this writing, the researcher uses a type of normative legal research supported by empirical data and this normative legal research uses law as a theoretical basis. In addition, the author uses an approach with a descriptive analysis method with research materials, namely primary, secondary and tertiary legal materials. The data analysis used in this study is descriptive analysis. The formulation of the problem in this study is (1) How is the implementation of law enforcement against perpetrators of criminal acts of theft of LPG gas cylinders in Tembilahan? (2) What are the causal factors that influence the rampant theft of LPG gas cylinders in Tembilahan. and the results of the research and discussion are (1) The implementation of law enforcement against perpetrators of criminal acts of theft of LPG gas cylinders in Tembilahan has been carried out well by the police, this can be seen in several cases that have been attached above starting from cases of theft with small losses to large losses have been handled well and the perpetrators have been handled by the authorities. (2) The factors that influence the rampant theft of LPG gas cylinders in Tembilahan are economic factors, lack of security systems, limited supervision, drug abuse and urgent needs as well as opportunities in adversity.